Program Mushafahah (Bersalaman) Sebagai Upaya Character Building Pada Siswa Sekolah Dasar Islam Swasta Pekanbaru - Pohan, Rahmadanni; Fitrianti, Leni; Siregar, Robiatul Hidayah (Sekolah Tinggi agama Islam Negeri (STAIN) Curup, 2017)
The study was administered at Private Islamic elementary school Pekanbaruwhich aimed to obtain objective data, factual, accurate and systematic regarding implementation Program as an attempt to shake the character building students of private Islamic elementary school Pekanbaru. Character is life mustika what distinguishes man from other creatures. Given the urgent and fundamen character, then the educational institution has a responsibility to incorporate them to the students in the school environment in general and in the process of learning, especially in order to form human character with various policies set out in the program within the school and the learning process. This study is a qualitative research case study type with a naturalistic approach in which researchers describe the study and case studies related to implementation Program as an attempt to shake the character building students of private Islamic elementary school Pekanbaru by direct observation, interview and documentation as data collection techniques. As for the informant is the head master, deputy superintendent of curriculum, deputy head of the student, the teacher and studens in grade five. The results of study showed that implementation Program as an attempt to shake went well with the pattern of habituation and modeling, but there is no planned evaluation and follow-up of the school. Keywords: Shake Hands, Character Building, Students